2018
DOI: 10.1186/s12875-018-0856-9
|View full text |Cite
|
Sign up to set email alerts
|

How general practitioners would deprescribe in frail oldest-old with polypharmacy — the LESS study

Abstract: BackgroundMany oldest-old (> 80-years) with multimorbidity and polypharmacy are at high risk of inappropriate use of medication, but we know little about whether and how GPs would deprescribe, especially in the frail oldest-old. We aimed to determine whether, how, and why Swiss GPs deprescribe for this population.MethodsGPs took an online survey that presented case-vignettes of a frail oldest-old patient with and without history of cardiovascular disease (CVD) and asked if they would deprescribe any of seven m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 56 publications
(65 reference statements)
1
31
0
4
Order By: Relevance
“…A mean of 6.5 drugs per patient resulted in our study. This is a significant result because this values is associated in literature with a greater risk of inappropriate prescriptions, DDI and ADR [12,13]. Belonging to the older age group (age > 85 years) was associated with the risk of polytherapy.…”
Section: Discussionmentioning
confidence: 94%
“…A mean of 6.5 drugs per patient resulted in our study. This is a significant result because this values is associated in literature with a greater risk of inappropriate prescriptions, DDI and ADR [12,13]. Belonging to the older age group (age > 85 years) was associated with the risk of polytherapy.…”
Section: Discussionmentioning
confidence: 94%
“…The characteristics of all of the included studies are described in table 1. The included studies had all been conducted in high-income developed countries, including Canada,36 37 USA,38–44 Netherlands,45 46 Australia,47 48 UK,49–51 Germany52–55 and Switzerland 56–58. Sample sizes ranged from 15 to 1169 patients and 5 to 92 clinicians in the quantitative studies, and 15 to 146 patients and 4 to 19 clinicians in the qualitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome of quality assessment based on each of the aforementioned tools is summarised in online supplementary appendix 2. The majority of the quantitative studies were cross-sectional in design,36 39 40 45–47 53 54 56–58 including the quantitative elements of the two mixed-methods studies. The other studies included one cohort study44 and one randomised controlled trial 52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, medications, including statins, are often continued until death . It has been reported that physicians do not feel confident about deprescribing cardiovascular preventive medication and survey studies have found considerable treatment variation in the advice regarding discontinuation of preventive medication . A likely contributing factor and an acknowledged barrier to deprescribing medications is the lack of evidence and clear guidance in clinical practice guidelines .…”
mentioning
confidence: 99%